Early postoperative mortality similar between cemented and uncemented hip arthroplasty: a register study based on Finnish national data - Ekman, Elina; Palomäki, Antton; Laaksonen, Inari; Peltola, Mikko; Häkkinen, Unto; Mäkelä, Keijo (Acta Orthopaedica, 2019)
Background and purpose — Implant survival of cemented total hip arthroplasty (THA) in elderly patients is higher than that of uncemented THA. However, a higher mortality rate in patients undergoing cemented THA compared with uncemented or hybrid THA has been reported. We assessed whether cemented fixation increases peri- or early postoperative mortality compared with uncemented and hybrid THA. Patients and methods — Patients with osteoarthritis who received a primary THA in Finland between 1998 and 2013 were identified from the PERFECT database of the National Institute for Health and Welfare in Finland. Definitive data on fixation method and comorbidities were available for 62,221 THAs. Mortality adjusted for fixation method, sex, age group, and comorbidities among the cemented, uncemented, and hybrid THA was examined using logistic regression analysis. Reasons for cardiovascular death within 90 days since the index procedure were extracted from the national Causes of Death Statistics and assessed separately. Results — 1- to 2-day adjusted mortality after cemented THA was comparable to that of the uncemented THA group (OR 1.2; 95% CI 0.24–6.5). 3- to 10-day mortality in the cemented THA group was comparable to that in the uncemented THA group (OR 0.54; CI 0.26–1.1), and in the hybrid THA group (OR 0.64, CI 0.25–1.6). Pulmonary embolism or cardiovascular reasons as a cause of death were not overrepresented in the cemented THA group. Interpretation — Early peri- and postoperative mortality in the cemented THA group was similar compared with that of the hybrid and uncemented groups.